"We're in This Together": Principals and Teachers as Partners and Learners in Lesson Study. (March 2019) - Lee, Valarie; Madden, Marjorie
This research proposes Lesson Study as a professional development structure that allows principals and teachers in secondary schools to meet the demands of English and disciplinary literacy standards. It is a collaborative study between a university and eight schools. The essential questions is, "How can Lesson Study broaden content knowledge and affect instructional leadership?" Data are analyzed using qualitative methods. Findings suggest the possibilities of Lesson Study in creating principal teacher partnerships to address challenges of practice in today's schools.